ANALYSIS OF THE IMPACT OF MODERN RETAIL ON BUYER INTEREST IN TRADITIONAL RETAIL, TILAMUTA DISTRICT - Wilda Sayi; William Indra S.Mooduto mooduto; Siske Anani (Journal of Economic, Business, and Administration (JEBA), 2023)
This study aims to determine the impact of the entry of modern retail on buyer interest in traditional retail in Tilamuta District. The method in this study uses descriptive qualitative methods with observational data collection techniques, in-depth interviews and documentation.The results of the study indicate that the entry of modern retail can be detrimental to traditional retail which is located adjacent to modern retail but there are still other traditional retailers that are not too disadvantaged by the entry of modern retail. Besides that, modern retail also has good facilities and has complete products so that buyers in traditional retail want to shop at modern retail. Traditional retail still has deficiencies in product completeness and inadequate facilities. However, other traditional retailers do not feel that modern retail is influential because the distance is not too close to modern retail. So that cooperation is needed between traditional retail and modern retail and the Tilamuta sub-district government in permitting the development of a modern retail business to be in accordance with laws issued by the central government.